Implementasi Kebijakan Pencegahan Pemberantasan Penyalahgunaan Dan Peredaran Gelap Narkoba (P4gn) Sebagai Rekayasa Sosial Dalam Memberantas Penyalahgunaan Narkoba Di Kota Surabaya - Adellia, Inge; Febrianti, Manda Ayu; Maulida, Siti Nurhaliza (Institut Riset dan Pengembangan Indonesia, 2023)
Drug circulation and use are serious problems experienced by several countries, one of which isIndonesia.In fact, this case has become a social phenomenon that needs special attention from the government andall levels of society. In handling narcotics, the government created the engineering of the Prevention ofEradication of Drug Abuse and Illicit Circulation (P4GN) as an effort to fight illegal drug abuse, especiallythe Surabaya area. The Mayor of Surabaya City issued Mayor Regulation Number 65 of 2014. Based onthis ratification, this study aims to explore how to implement P4GN regulations in dealing with drug abuse,especially in Surabaya. The method used in this study is descriptive using a qualitative approach with thefocus of research in the form of policy implementation theory by Van Meter and Van Horn (1975) andmacrosocial theory from Thomas Hobbes. The data collection technique used is by literature study. Theresults showed that the P4GN policy as a form of social engineering in eradicating drugs in Surabaya hasnot been fully successful because the standards/measures and policy objectives have not been well realizedbecause drug cases continue to increase, but BNN Surabaya already has competent and professionalhuman resources. As well as the condition of the social environment shown by the community is lessconcerned about the dangers of drugs and also from the relationship of implementation with the economicconditions of the community which results in drug circulation and abuse still exists in the city of Surabaya.